2020
DOI: 10.15275/rusomj.2020.0104
|View full text |Cite
|
Sign up to set email alerts
|

Parameter dynamics of the physical development in children and youth of Volgograd region (Russian Federation) using the percentile method

Abstract: The study objective was to analyze the parameters of physical development (body length and weight) in children and youth 7-17 yo – students of Volgograd region educational institutions over 2012-2016 using the percentile method. Material and methods — We examined 4,367 school students, of which 2,056 and 2,311 were boys and girl, correspondingly. The body lengths and weights were assessed by conventional methods. The results were processed using the programs Statistica 6.0 and MATLAB 7. Results — The values of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…The study showed the centenary dynamics, which is characterized by various trends in differences between anthropometric characteristics and indicators of biological development of school girls. Long-term trends of changes in physical development indicators were also noted by other authors [1,3,13,[35][36][37][38]. In most European countries, at the end of the XX -beginning of the XXI centuries, was noted the stabilization of physiological and growth processes with a simultaneous increase in body weight.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…The study showed the centenary dynamics, which is characterized by various trends in differences between anthropometric characteristics and indicators of biological development of school girls. Long-term trends of changes in physical development indicators were also noted by other authors [1,3,13,[35][36][37][38]. In most European countries, at the end of the XX -beginning of the XXI centuries, was noted the stabilization of physiological and growth processes with a simultaneous increase in body weight.…”
Section: Discussionsupporting
confidence: 67%
“…The current situation in Russia and the world is characterized by a high prevalence of noncommunicable diseases among children and adolescents, which is largely due to global lifestyle changes -the spread of unbalanced nutrition and sedentary lifestyle, uncontrolled use of electronic devices, reduction in medical activity, and many others [1,2]. Consequently, early diagnosis of premorbid conditions by indicators that are sensitive to the effects of risk factors for the development of diseases is of particular importance [3,4].…”
Section: Introductionmentioning
confidence: 99%